Effect of the COVID-19 Pandemic on Neurology Trainees' Education and Practice - Farheen, Amtul; Grogan, James; Jens, William; Maxwell, Christina; Benameur, Karima (RRNMF Neuromuscular Journal, 2021)
Objective: The COVID-19 pandemic has rapidly changed the neurology training landscape. The study was designed to assess the effects of COVID-19 on the education, practice, and well-being of US neurology trainees.Methods: A 36-item survey was distributed to neurology residents and fellows in the United States through various media platforms.Results: Over an 8-week period, 286 responses were received, 285 were included. Almost all (93%) trainees were in an academic setting. Tele-neurology use by trainees was minimal (13%) prior to the pandemic; however, during the pandemic 91% reported using it. A majority (84%) of trainees did not receive training in tele-neurology prior to the pandemic. Most trainees felt that the pandemic impacted their education with fewer lectures being available, and 77% resorted to getting lectures from outside institutions. Tele-lecturing with video conferencing was the most common mode of education during the pandemic. A third (33%) of trainees felt that they did not have enough PPE during the pandemic. Most trainees worried about exposing themselves or their families to COVID-19, and had increased stress levels.Conclusion: This study demonstrates that most neurology trainees had no training nor exposure to tele-neurology prior to the pandemic, and were rapidly thrusted into tele-neurology during the pandemic. Trainees had an overall negative educational impact, and were stressed during the pandemic. Use of technology and availability of outside institutions’ lectures were most helpful to continue with educational activities during this time.